2000
DOI: 10.1152/ajprenal.2000.278.3.f388
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2interaction with AVP: effects on AQP2 phosphorylation and distribution

Abstract: Prostaglandin E(2) (PGE(2)) antagonizes the action of arginine vasopressin (AVP) on collecting duct water permeability. To investigate the mechanism of this antagonism, rat renal inner medulla (IM) was incubated with the two hormones, and the phosphorylation and subcellular distribution of the water channel, aquaporin-2 (AQP2) were studied. Using a phosphorylation state-specific AQP2 antibody, we demonstrated that AVP stimulates AQP2 phosphorylation at the Ser(256) protein kinase A consensus site in a time- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 53 publications
(60 reference statements)
7
103
0
Order By: Relevance
“…sacodyl activates macrophages in the colon (24,29). Furthermore, TNF-␣ (9,19,38) and PGE 2 (25,39) decrease the expression levels of AQPs. Based on this, we examined whether bisacodyl directly activated macrophages and caused the secretion of TNF-␣ and PGE 2 using Raw264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sacodyl activates macrophages in the colon (24,29). Furthermore, TNF-␣ (9,19,38) and PGE 2 (25,39) decrease the expression levels of AQPs. Based on this, we examined whether bisacodyl directly activated macrophages and caused the secretion of TNF-␣ and PGE 2 using Raw264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates the possibility that PGE 2 is involved in the drastic and immediate decrease in AQP3 in the mucosal epithelial cells in the colon induced by bisacodyl administration. Although the mechanism by which PGE 2 decreases AQP3 is not yet clear, it may increase the endocytosis and degradation of AQP3 (25,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that inhibition of GSK3␤ by lithium results in enhanced renal COX2 expression in interstitial cells, leading to an increase in local PGE(2) excretion (18), that in turn may counteract AVP actions by causing endocytic retrieval of AQP2 from the collecting duct plasma membrane, thus impairing urinary concentrating ability (20). GSK3␤ knockout mice die from liver degeneration (21); thus, the consequence of GSK3␤ gene deletion on kidney function has yet to be examined.…”
Section: Regulation Of Pkb/akt By Lithium and Its Role In Cell Survivalmentioning
confidence: 99%
“…We have demonstrated that P2Y 2 receptor-mediated PGE 2 release is markedly enhanced in physiological polyuria induced by water loading, and blunted in oliguria caused by water deprivation or chronic dDAVP (V 2 receptor-specific analogue of AVP) infusion in rats [31,32]. PGE 2 antagonises AVP-stimulated water permeability in the medullary collecting duct [7,9], an effect that is partly due to activation of EP (E-prostanoid)3 receptormediated retrieval of AQP2 from the apical membrane [13]. In addition, PGE 2 can chronically elevate phoshoinositides and thus potentially reduce the cAMP levels (Fig.…”
Section: Physiology Of the P2y 2 Receptor In The Collecting Ductmentioning
confidence: 88%
“…Apart from AVP, a variety of autocrine and paracrine agents, such as prostaglandin E 2 (PGE 2 ), endothelin and extracellular nucleotides (ATP/UTP), can regulate collecting duct water transport [7][8][9][10][11][12][13][14]. Acting through their respective receptors, and the associated phosphoinositide signalling pathway, these agents decrease AVP-stimulated osmotic water permeability in the collecting duct (Fig.…”
Section: Non-avp Regulators Of Collecting Duct Functionmentioning
confidence: 99%